Red sun and Merlin unchained - Rudkin, David, 1936- (Intellect Books - Play Text Ser., 2011)
Red Sun and Merlin Unchained are the most recent original stage works by one of the most acknowledged yet neglected dramatists of our time. Red Sun is a two-hander, tightly tethered within the classical unities of theme and space and the span of a single day. Merlin Unchained is an explosive, multitudinous epic, crossing continents and centuries and passing between worlds. Yet though technically so contrasting, both works speak with the same distinctive voice, offering an exhilarating and sometimes disturbing challenge to the cultural and political perceptions of a contemporary audience, and e.